2021
DOI: 10.1016/j.scitotenv.2020.142533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 lockdown on global air quality and health

Abstract: The COVID-19 pandemic has put much of the world into lockdown, as one unintended upside to this response, the air quality has been widely reported to have improved worldwide. Existing studies examine the environmental effect of lockdowns at a city- or country-level, few examines it from a global perspective. Using a novel COVID-19 government response tracker dataset, combining the daily air pollution data and weather data across 597 major cities worldwide between January 1, 2020, and July 5, 2020, this study q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
135
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 23 publications
11
135
1
2
Order By: Relevance
“…The prevention and control measures taken by these countries have greatly reduced the transmission rates of COVID-19 ( Koyama et al, 2020 ). With the large-scale shutdowns and traffic restrictions, the aerosol pollution had a general corresponding decrease in levels ( Zhou et al, 2012 ; Liu et al, 2021 ; Shi et al, 2021 ). The results of aerosol concentration changes in different regions during the COVID-19 lockdown are summarized in Fig.…”
Section: Changes In Aerosol Pollution During Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…The prevention and control measures taken by these countries have greatly reduced the transmission rates of COVID-19 ( Koyama et al, 2020 ). With the large-scale shutdowns and traffic restrictions, the aerosol pollution had a general corresponding decrease in levels ( Zhou et al, 2012 ; Liu et al, 2021 ; Shi et al, 2021 ). The results of aerosol concentration changes in different regions during the COVID-19 lockdown are summarized in Fig.…”
Section: Changes In Aerosol Pollution During Covid-19mentioning
confidence: 99%
“…The large reduction of human activities has significantly improved air quality in many areas during the control of COVID-19. Compared with the pre-lockdown period, the concentrations of PM 10 (14–20%) and PM 2.5 (7–16%) in 597 major cities in the world have decreased significantly ( Liu et al, 2021 ). For the areas with more serious air pollution problems, the improvement of the aerosol is greater, and the decrease of PM 2.5 is greater than that of PM 10 ( Fig.…”
Section: Changes In Aerosol Pollution During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…were largely limited in many countries. Although the harm caused by COVID-19 is very large, several studies found that these control measures could greatly affect air pollutants emissions and the air quality, and the premature deaths due to improved air quality declined in many countries and regions [ 174 , 175 , 176 , 177 ], suggesting the control of air pollution should be more strengthened.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Liu et al (2021) analyze the effects of COVID-19 lockdown in about 600 major cities worldwide and show that NO 2 air quality index value falls more precipitously relative to the pre-lockdown period, followed by PM 10 , SO 2 , PM 2.5 , and CO, but the level of O 3 increases. Moreover, Liu et al (2021) argue that the impact of COVID-19 lockdown on environmental pollution generates health bene ts in terms of the expected averted premature deaths due to air pollution declines. In general, the evidence that COVID-19 outbreaks have reduced levels of air pollution and detrimental effects of polluted environment on human health is now rarely contested.…”
Section: The Problem and Goal Of The Investigationmentioning
confidence: 99%